2017
DOI: 10.1159/000458746
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Genome Composition and Recombination between Homoeologous Chromosomes in <b><i>Festulolium</i></b> (<b><i>Festuca × Lolium</i></b>) Cultivars

Abstract: Festulolium are hybrids between fescue (Festuca) and ryegrass (Lolium) species and combine high seed yield of ryegrasses with abiotic stress tolerance of fescues. Chromosomes of Festuca and Lolium present in Festulolium freely pair and recombine, which results in highly variable progeny where every single plant has a unique chromosome constitution. Thus, the stability of the genomic composition in Festulolium cultivars is an important issue. In this work, we used in situ hybridization to examine the genomic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In our previous work, we confirmed that amphiploid L. multiflorum × F. pratensis cultivars were relatively stable over three consecutive generations. Despite a large variability within the populations, the genomic composition did not change significantly, and the Festuca chromatin was not eliminated any further [18]. Similarly, Zwierzykowski et al reported that chromosomes of F. pratensis were gradually replaced by those of L. multiflorum in six consecutive generations of hybrids but became stabilized in the F7-F8 generations without any additional elimination of Festuca chromatin [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous work, we confirmed that amphiploid L. multiflorum × F. pratensis cultivars were relatively stable over three consecutive generations. Despite a large variability within the populations, the genomic composition did not change significantly, and the Festuca chromatin was not eliminated any further [18]. Similarly, Zwierzykowski et al reported that chromosomes of F. pratensis were gradually replaced by those of L. multiflorum in six consecutive generations of hybrids but became stabilized in the F7-F8 generations without any additional elimination of Festuca chromatin [20].…”
Section: Discussionmentioning
confidence: 98%
“…The continuity of Festuca-chromatin elimination in advanced breeding material is questionable. In our previous work, we analyzed three consecutive generations of three registered amphiploid xFestulolium cultivars [18]. We found that despite high genetic variability within each population, the proportion of parental genomes was relatively stabilized without apparent Festuca-chromatin elimination in subsequent generations.…”
Section: Introductionmentioning
confidence: 95%
“…While amphiploids display relatively stable genome composition and no further shifts towards Lolium genome, elimination of introgressed segment(s) has been observed in the introgression forms. Stabilization of the hybrid genome in amphiploid cultivars is observed at about 2:1 proportion of Lolium vs. Festuca chromosomes (Kopecký et al 2017). This ratio probably creates optimal combinations of parental alleles and the highest heterosis.…”
Section: Genome Balance and Stability Of Hybridsmentioning
confidence: 98%
“…Despite the formation of quadrivalents and meiotic irregularities leading to frequent aneuploidy (up to 80 % in cvs. Hostýn and Perseus), fertility is high and seed set is sufficient for commercial production (Ghesquiere et al 2010, Kopecký et al 2017.…”
Section: Genome Balance and Stability Of Hybridsmentioning
confidence: 99%
See 1 more Smart Citation